FROST INVESTIGATION 1945-1946. APPENDIX 5. REPORT ON PIERRE AIRFIELD, PIERRE, SOUTH DAKOTA. APPENDIX 6. REPORT ON SIOUX FALLS AIRFIELD, SIOUX FALLS, SOUTH DAKOTA. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1946)
The report presents the results of the frost investigation conducted at Pierre Airfield, Pierre, South Dakota, Sioux Falls Airfield, Sioux Falls, S. D., during the period 14 November 1945 through June 1946, and supplements the results of the investigations conducted during the period 13 November 1944 through 1 May 1945, and reported on in June 1945. The investigation included the observation of subsurface temperatures, frost penetration, pavement heaving and ground water table. See also Appendix 4, AD-712 354 and Appendices 7/9, AD-712 355. Prepared in cooperation with Corps of Engineers, Omaha, Neb. Missouri River Div.